O lirismo em györgy lukács - da Silva, Arlenice Almeida [UNESP] (My University, 2009)
The paper aims to examine the treatment of lyrical in the aesthetics work of the young Lukács. In The Soul and the Forms the author examines the poetry of Stefan George, fi nding on it formal elements that point out to the emergence of a new lyricism. This signifi cant form allows the author to introduce an approach of the concept of modernity, in critical and phenomenological bias. Work that will be completed in The theory of Love, when the lyric trend will be exacerbated, contaminating and altering the settings of the other genera.
Keywords: Aesthetics; Gender; Poetry; Significant structure